Multivisual Animation Character 3D Model Design Method Based on VR Technology - Leiming Li; Wenyao Zhu; Hongwei Hu (Complexity)
For VR systems, one of its core parts is to present people with a real and immersive 3D simulation environment. This paper uses real-time computer graphics technology, three-dimensional modeling technology, and binocular stereo vision technology to study the multivisual animation character objects in virtual reality technology; designs a binocular stereo vision animation system; designs and produces a three-dimensional model; and develops a virtual multivisual animation scene application. The main research content and work performed in the text include the research of the basic graphics rendering pipeline process and the analysis and research of each stage of the rendering pipeline. It mainly analyzes the 3D graphics algorithm used in the three-dimensional geometric transformation of computer graphics and studies the basic texture technology, basic lighting model, and other image output processes used in the fragment processing stage. Combined with the development needs of the subject, the principles of 3D animation rendering production software and 3D graphics modeling are studied, and the solid 3D model displayed in the virtual reality scene is designed and produced. This article also reflects the application of virtual reality in multivisual animation character design from the side, so it has realistic value and application prospects.